Muebles, nudos, escritos y culturas - Mazzoldi, Bruno (CALLE14: revista de investigación en el campo del arte, 2011)
On the edge of a freeway already stepped by Bradbury, it is sustained that writing happens and that —from the corner of a school in the Department of Oruro, Bolivia, up to the niche of Walter Benjamin’s childhood in Berlin— the inscription’s material and timely environment corresponds to the theater of a ferocious literality that refuses to be merely read or deciphered. This lyrical essay is elaborated submerging into two marginal notes that, contradicting their own marginalization, manifest the emergency of an ultracellular mobility, whether pointing out the misunderstanding consisting in identifying with the heaviness of Rimbaud’s “sitters” with the dream of the “furnished man” according to Benjamin, or denouncing some misrepresentations of Derrida as the fantasy product of those who oppose exhibition and secret, significant pact and magic impact —all that without scorning degreiffian-lezamesques neologisms, for the sake of a fusion of genres, disciplines and cultural adhesions that are not merely brought to the story.